Les communautés agri-alimentaires viables, une coviabilité pour un renouvellement des communs ? - Béatrice Maurines (VertigO)
The cause addressed here is that of agri-food, supported by social and solidarity structures that participate in the constitution of “sustainable agri-food communities”. These communities are hybrid spaces of production and consumption that value “eating well” in urban and rural areas and are built around shared values stemming from agricultural and food alternatives. Here, we clarify the ways in which these structures think and act, pointing out that what drives them is to inscribe their projects in processes of sustainability. We first present three configurations of viable agri-food communities: the collective farm of Les Volonteux, and in an urban setting, the associative assemblages of the cluster for cooperation on food le Bol and the Maison engagée et solidaire de l'alimentation, both based in the Lyon area. These situated configurations highlight the multi-dimensional modalities of viability and hinge on ongoing innovations to jointly address ecological and economic crises. By comparing them, we can clarify their socio-political references in favor of agri-ecological change and confirm that co-viability is intrinsically linked to the notion of viable agri-food communities. This concept prompts us to reflect on how they are linked to the renewal of the concept of the commons.